The Transformative Role Of Library Blogs In Marketing Of Library And Information Products And Services (Journal of Namibian Studies : History Politics Culture, 2023)
The article deals with the transformative role played by library blogs for information dissemination and community engagement. The article talks about adaptation of libraries to the changing needs. To cater to a large population, present on the internet library blogs and websites have become important means for attracting younger generation. The article also deals with the challenges and limitations of the library blog.